Tomography systems and sound manipulation using acoustic - Abdul Hamid, Siti Zaleha; Hamidon, Siti Nur Nasha Azlika; Abdul Rahim, Herlina; Abdul Rahim, Ruzairi (Malaysian Society for Computed Tomography & Imaging Technology (MyCT), 2018)
Conventional materials in noise reduction such as concretes, woods, foams and glasses is widely used in building to reduce noise in our surroundings. However, these materials exhibit very low capability in reducing low frequency noise. Metamaterials are introduced to provide better sound reduction in low frequency replacing the conventional bulky materials with less weight and cost. Hence, this study performed to investigate the feasibility of acoustic metamaterials in sound reduction. Five samples of acoustic enclosures are fabricated using different materials with dimension of 100 mm3. Wood acoustic enclosure are fabricated manually while acrylonitrile butadiene styrene (ABS), poly lactic acid (PLA), PLA with metamaterial (1 mm thickness of cavity w ) and PLA with metamaterial (5 mm thickness of cavity w ) acoustic enclosures are fabricated digitally using three-dimensional (3D) printing method. Performance analysis for acoustic enclosure samples was measure based on decibel drop, d to show the difference in sound pressure level before and after acoustic enclosure is placed on the sound source. PLA acoustic enclosure with metamaterial of 5 mm thickness is able to reduce sound level better than the rest of acoustic enclosures samples with the highest reduction of sound pressure level, 26.1 dB occurred on 800 Hz and proved that a greater thickness of metamaterial exhibit better sound reduction.